Analisis Pelaksanaan Pendidikan Karakter di MA Madania Bantul Yogyakarta - Muhammad Zaylani; Muhammad Wasith Achadi (ALSYS, 2026)
This study examines the implementation of character education at MA Madania Bantul Yogyakarta, a social-based madrasah that provides free education for students from economically disadvantaged families. The aim of this research is to analyze the background, planning, implementation, organization, evaluation, and outcomes of character education implementation within Islamic Religious Education learning. This study employed a qualitative method with a descriptive approach using interviews, observations, and documentation. The findings show that character education at MA Madania is integrated into all aspects of the madrasah through collaboration among teachers, dormitory staff, and student organizations, so that the program successfully shapes students to be religious, independent, disciplined, and highly socially engaged. The study concludes that the character education model at MA Madania represents a good practice that contextually and sustainably integrates Islamic, social, and entrepreneurial values into Islamic Religious Education learning.